Hypervirulent carbapenem-resistant Klebsiella pneumoniae causing highly fatal meningitis in southeastern China - Huang, Na; Jia, Huaiyu; Zhou, Beibei; Zhou, Cui; Cao, Jianming; Liao, Wenli; Liu, Shixing; Wang, Lingbo; Chen, Liqiong; Chen, Lijiang; Zhou, Tieli; Ye, Jianzhong (Frontiers in Public Health, 2022)
Klebsiella pneumoniae (K. pneumoniae) is one of the most common causes of bacterial meningitis worldwide. The purpose of this study was to investigate the clinical and microbiological characteristics of K. pneumoniae meningitis, as well as the association of antimicrobial resistance, virulence, and patient prognosis. The clinical data of patients with K. pneumoniae meningitis from 2014 to 2020 in a tertiary teaching hospital were retrospectively evaluated. Antimicrobial susceptibility profiles were performed by the agar dilution method and broth microdilution method. The isolates were detected for virulence-related genes, resistance genes, capsular serotypes, and molecular subtypes. A total of 36 individuals with K. pneumoniae meningitis were included in the study, accounting for 11.3% (36/318) of all cases of bacterial meningitis. Of the 36 available isolates, K1, K47, and K64 were tied for the most frequent serotype (7/36, 19.4%). MLST analysis classified the isolates into 14 distinct STs, with ST11 being the most common (14/36, 38.9%). Carbapenem resistance was found in 44.4% (16/36) of the isolates, while hypervirulent K. pneumoniae (HvKP) was found in 66.7% (24/36) of the isolates. The isolates of hypervirulent carbapenem-resistant K. pneumoniae (Hv-CRKP) were then confirmed to be 36.1% (13/36). Importantly, individuals with meningitis caused by Hv-CRKP had a statistically significant higher mortality than the other patients (92.3%, 12/13 vs. 56.5%, 13/23; P < 0.05). The high percentage and fatality of K. pneumoniae-caused meningitis, particularly in Hv-CRKP strains, should be of significant concern. More effective surveillance and treatment solutions will be required in future to avoid the spread of these life-threatening infections over the world.